In vitro interactions of berbamine hydrochloride and azoles against Aspergillus fumigatus - Heng Zhang; Yizheng Zhou; Hanmo Yang; Xinyi Tao; Yinping Chen; Fuqiang Dong; Yi Sun (Microbiology Spectrum)
ABSTRACT The growing resistance of Aspergillus to azoles poses a significant challenge in treating invasive fungal infections. This study aimed to investigate the synergistic effect of berbamine hydrochloride (BBM) combined with azoles in treating Aspergillus fumigatus and explore the role of efflux pump inhibition in this synergy. The efficacy of combining BBM with itraconazole (ITC), voriconazole (VOR), and posaconazole (POS) was tested against 69 A. fumigatus strains that had been identified using the M38-A3 broth microdilution method. quantitative reverse transcription PCR (RT-qPCR) was used to measure gene expression related to synergy, while flow cytometry was employed to assess mitochondrial reactive oxygen species (ROS) levels, and Rhodamine 6G exocytosis assays were performed to quantify efflux pump activity. BBM alone showed no significant antifungal activity. BBM combined with POS exhibited synergy against 66 strains (95.7%), while two clinical isolates (Af05/Af08) and one defective strain (Δcdr1B) showed no synergy. Synergy with ITC was observed in three strains (4.3%), but not with VOR. In the non-synergistic Af05 and Af08 strains, the expression of the cdr1B gene was significantly lower compared to wild-type (WT) strains. ROS levels increased significantly in WT with POS and BBM combination therapy, but not in the defective strains. Glucose uptake was also reduced in the POS-BBM combination. BBM enhances azole sensitivity in A. fumigatus primarily by inhibiting the cdr1B-mediated efflux pump, supported by reduced Rhodamine 6G exocytosis and synergy loss in cdr1B-deficient strains. ROS accumulation and metabolic disruption may further contribute to this synergy. Targeting efflux pumps with BBM provides a novel strategy to combat azole resistance.IMPORTANCEThe combination of berbamine hydrochloride and posaconazole effectively enhances azole sensitivity in Aspergillus fumigatus by reducing efflux pump activity and increasing reactive oxygen species levels. The findings offer a promising strategy to combat azole resistance in invasive fungal infections.